2018
DOI: 10.1002/mbo3.742
|View full text |Cite
|
Sign up to set email alerts
|

Selecting lipopeptide‐producing, Fusarium‐suppressing Bacillus spp.: Metabolomic and genomic probing of Bacillus velezensis NWUMFkBS10.5

Abstract: The results of this study indicate that the maize rhizosphere remains a reservoir for microbial strains with unique beneficial properties. The study sought to provide an indigenous Bacillus strain with a bioprotective potential to alleviate maize fusariosis in South Africa. We selected seven Bacillus isolates (MORWBS1.1, MARBS2.7, VERBS5.5, MOREBS6.3, MOLBS8.5, MOLBS8.6, and NWUMFkBS10.5) with biosuppressive effects against two maize fungal pathogens ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 119 publications
0
25
0
Order By: Relevance
“…In this study, compounds identified at m / z values of 1461.8, 1489.7, and 1490.9 suggest the presence of fengycins in the supernatant of cultivation broth obtained by cultivation of B. velezensis IP22 ( Figure 7 ) [ 39 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…In this study, compounds identified at m / z values of 1461.8, 1489.7, and 1490.9 suggest the presence of fengycins in the supernatant of cultivation broth obtained by cultivation of B. velezensis IP22 ( Figure 7 ) [ 39 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 75%
“…According to de Fillippi et al [ 43 ], fengycins A have been identified in m / z range of 1464–1506 [M+H] + , while fengycins B have been detected in the m / z range of 1462–1490 [M+H] + . Adeniji et al [ 44 ] identified fengycins in the m / z range of 1449.9–1515.9. Recent study has confirmed antibacterial effect of fengycins against Xanthomonas axonopodis pv.…”
Section: Discussionmentioning
confidence: 99%
“…The genome sequence conditions, protocols, assembly, annotation, data mining, and in silico analysis of this B. velezensis strain (NWUMFkBS10.5) have been previously documented by Adeniji et al (9). Briefly, genomic DNA of the strain was extracted using the Zymo Research (ZR) soil microbe DNA miniprep genomic isolation kit.…”
Section: Announcementmentioning
confidence: 99%
“…With a view to providing an indigenous biocontrol agent against the etiological agents (e.g., Fusarium verticillioides, Fusarium culmorum, and Fusarium graminearum) of fusariosis, a worldwide disease that affects the quality and production of major cereal grains, we report here the draft genome sequence of an anti- Fusarium and antioxidant-producing B. velezensis strain isolated from the maize rhizosphere in the North West region of South Africa (8, 9). A pure culture of isolate NWUMFkBS10.5 was obtained from a distinct colony after 5 g of rhizospheric soil from the maize farm was cultured on HiCrome (Oxoid) selective Bacillus commercial agar plates following the manufacturer’s instructions.…”
Section: Announcementmentioning
confidence: 99%
See 1 more Smart Citation